Wood properties and transcriptional responses of poplar hybrids in mixed cropping with the nitrogen-fixing species Robinia pseudoacacia. (4th November 2020) - Euring, Dejuan; Janz, Dennis; Polle, Andrea
Abstract: Cultivation of fast-growing tree species is often confined to marginal land. Mixed cropping with Robinia pseudoacacia, a legume tree species that forms a symbiosis with N2 -fixing bacteria, has been proposed to be a measure to improve soil fertility and to achieve beneficial effects on the cocultivated tree species. The goal of our study was to examine the influence of a Robinia mixture on wood chemistry, anatomy and gene expression in poplar. We hypothesized that annual wood growth is stimulated in species mixtures due to the positive effects of Robinia on nitrogen availability and complementary resource use. Alternatively, we hypothesized that competition, especially for water, has negative effects on the wood growth of poplar. We used two commercial biomass clones, Hybride 275 (H275, Populus trichocarpa × Populus maximowiczii ) and Max1 ( Populus nigra × P. maximowiczii ), which were planted at two locations with contrasting soil fertility in monoculture or mixed plots with Robinia to investigate the annual wood increment, wood nitrogen and δ 13 C, wood anatomy (length, cell wall thickness, lumina and frequencies of fibers and vessels) and transcriptional profiles in the developing xylem of 4-year-old stems. In a mixture with Robinia, the annual stem increment was reduced, nitrogen in wood was enhanced, δ 13 C in wood was decreased, vessel and fiber frequencies were increased and fiber lengths and fiber lumina were decreased. Transcriptional profiles showed stronger differences between the genotypes and sites than between mono and mixed cultivation. The transcriptional abundances of only one gene (the putative nitrate transporter, NRT1.2 ) and one gene ontology term ('immune system process') were significantly enriched in wood-forming tissues in response to the mixture, irrespective of the poplar genotype and growth location. Weighted gene coexpression network analyses extracted gene modules that linked wood nitrogen mainly to vessel traits and wood δ 13 C with fiber traits. Collectively, molecular and anatomical changes in poplar wood suggest beneficial effects on the water and N supply in response to the mixture with Robinia. These alterations may render poplars less drought-susceptible. However, these benefits are accompanied by a reduced wood increment, emphasizing that other critical factors, presumably light competition or allelopathic effects, overrule a potential growth stimulation.